(untitled) (Revista Innova Educación, 2021)
The objective of this article was to relate the exercise of citizenship with the practice of sports in the Colombian post-conflict context. The methodology used was documentary research. The result was that it is possible from such a combination to promote values that help improve coexistence, based on the principles of respect for others, tolerance, and the exercise of solidarity. It is concluded that such a combination is a way of contributing to peace in Colombia, during the post-conflict period that the country is currently experiencing. This article addresses how sport can contribute to the consolidation of a new exercise of citizenship, understanding that the teacher, regardless of their specific knowledge, is called to promote the exercise of citizenship in a democratic and free way among their students, to knowing that the values that each sport demands go hand in hand with those that are required for the democratic exercise.